2021
DOI: 10.1021/jacs.1c06863
|View full text |Cite
|
Sign up to set email alerts
|

Protodeboronation of (Hetero)Arylboronic Esters: Direct versus Prehydrolytic Pathways and Self-/Auto-Catalysis

Abstract: The kinetics and mechanism of the base-catalyzed hydrolysis (ArB(OR) 2 → ArB(OH) 2 ) and protodeboronation (ArB(OR) 2 → ArH) of a series of boronic esters, encompassing eight different polyols and 10 polyfluoroaryl and heteroaryl moieties, have been investigated by in situ and stopped-flow NMR spectroscopy ( 19 F, 1 H, and 11 B), pH-rate dependence, isotope entrainment, 2 H KIEs, and KS-DFT computations. The study reveals the phenomenological stability of boronic esters under basic aqueous−organic conditions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 145 publications
1
49
0
Order By: Relevance
“…In addition, base-sensitive heteroaryl boronic acids ( 2l – 2p ) efficiently provided the desired products ( 3ak – 3ao ) in excellent yield (86–99%). Unfortunately, 2-pyridyl boronic acid pinacol ester ( 2q ), which is highly sensitive to protodeboronation, did not react under the applied solid-state conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, base-sensitive heteroaryl boronic acids ( 2l – 2p ) efficiently provided the desired products ( 3ak – 3ao ) in excellent yield (86–99%). Unfortunately, 2-pyridyl boronic acid pinacol ester ( 2q ), which is highly sensitive to protodeboronation, did not react under the applied solid-state conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to being directly catalyzed by water, the protodeboronation of arylboronic acids and arylboronic acid pinacol esters is known to occur under acidic and basic conditions and by reaction with various metal salts. [243][244][245] Polyfluorinated and 2-heteroaryl boronic acids have been revealed to be exceptionally unstable and readily undergo deboronation. [246] The mechanism by which aryl boronic acids undergo base-induced protodeboronation is proposed to commence by the formation of an arylboric acid (Ar-B(OH) 3 -) (Scheme 71).…”
Section: Synthesis Of Biaryls 69 Using Suzuki-miyaura Cross-coupling ...mentioning
confidence: 99%
“…The base-induced protodeboronation of aryl boronic acid pinacol esters is believed to proceed via a similar mechanism. [245] Scheme 71: Proposed mechanism for the base-induced protodeboronation of arylboronic acids. [243,244] The strong electronegative effect exhibitied by the trifluoromethyl group of pinacol ester 83d is presumably sufficient to destabilize the C-B bond, causing deboronation to form 4-(trifluoromethyl)aniline.…”
Section: Synthesis Of Biaryls 69 Using Suzuki-miyaura Cross-coupling ...mentioning
confidence: 99%
“…Recently, Lloyd-Jones et al investigated the kinetics and mechanism of the base-catalyzed hydrolysis and protodeboronation of a series of fluorinated boronic compounds. They found that pinacol boronic esters display a unique stability at a high pH compared to other commonly employed esters [ 34 ].…”
Section: Introductionmentioning
confidence: 99%